A HEMATOLOGICAL CHAMELEON: THE TRANSITION FROM MDS TO NON-SECRETORY MULTIPLE MYELOMA AND BACK – UNRAVELİNG DIAGNOSTIC COMPLEXITIES AND ADAPTING THERAPEUTIC PATHWAYS - Candaş Mumcu; Ceren Kısa; Birol Güvenç (Hematology, Transfusion and Cell Therapy)
Objective: The interplay between myelodysplastic syndrome (MDS) and non-secretory multiple myeloma (MM) can confound even seasoned hematologists, particularly when these conditions shift over time. This case presents a remarkable instance of a patient transitioning from MDS to non-secretory MM and then reverting back to MDS, underscoring the need for meticulous monitoring and adaptable treatment strategies when dealing with complex hematological landscapes. Case Presentation: An 82-year-old patient initially sought care for severe anemia, leading to a diagnosis of MDS based on bone marrow findings. At this point, no signs of MM were present. However, later investigations—specifically urine immunofixation—suggested the emergence of non-secretory MM, which was confirmed through a second bone marrow biopsy.The patient began treatment with Velcade, Revlimid, and Dexamethasone (VRD), showing marked improvement in anemia. Yet, given the patient's age and frailty, hematopoietic stem cell transplantation (HSCT) was not considered viable. As treatment progressed, the regimen evolved to ixazomib, lenalidomide, and dexamethasone, achieving remission for several years.Despite this stability, a resurgence of anemia signaled a reversion to MDS. A fresh treatment strategy was introduced, combining azacitidine, low-dose lenalidomide, and erythropoietin, aimed at maintaining functionality and quality of life without aggressive interventions. Discussion: This case encapsulates the volatile nature of hematologic disorders, illustrating how diseases like MDS and non-secretory MM can morph and evolve. It emphasizes the importance of adaptive management, especially in elderly patients, where rigid treatment paradigms may fall short. The use of lenalidomide throughout the patient's journey reflects its dual utility in both plasma cell and myeloid disorders, while also sparking questions about whether prolonged exposure could influence secondary disease development. Conclusion: The patient's journey through MDS, MM, and back again underscores the critical need for dynamic reassessment, vigilance, and personalized care. This case exemplifies the blurred boundaries between plasma cell dyscrasias and myeloid neoplasms, raising thought-provoking questions about disease progression and therapeutic strategies. In navigating these complexities, clinicians are reminded of the importance of flexible, patient-centered approaches in managing intricate hematological disorders.